2022
DOI: 10.3390/plants11030419
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biological Activity of Fiber-Type Cannabis sativa L. Aerial Parts at Different Growth Stages

Abstract: Currently, there is a renewed interest in cannabis-related products in different fields because of the rich phytocomplex of this plant, together with its fiber and agricultural features. In this context, the current study aims to chemically characterize different samples of fiber-type Cannabis sativa L. grown in Italy as a potential health promoting source. An ultrasound-assisted solid-liquid extraction (UA-SLE) method was first developed and optimized to obtain a fingerprinting of the investigated phytocomple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…This observation is consistent with the reports from Mastellone et al . that indicated the cannabinoid content from the stem of Cannabis sativa L. was independent of the growth stage of harvesting and the content showed a slight increase at the stage closer to flowering [11]. Free fatty acid (FFA) composition in the hemp was consistent with previous studies [42], which highlighted that palmitic acid was the most abundant FFA, followed by oleic acid and stearic acid.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This observation is consistent with the reports from Mastellone et al . that indicated the cannabinoid content from the stem of Cannabis sativa L. was independent of the growth stage of harvesting and the content showed a slight increase at the stage closer to flowering [11]. Free fatty acid (FFA) composition in the hemp was consistent with previous studies [42], which highlighted that palmitic acid was the most abundant FFA, followed by oleic acid and stearic acid.…”
Section: Resultssupporting
confidence: 85%
“…9: 211699 compared with the tops and the growth stage of the plant had only a minor influence on the cannabinoid content (around 202-253 µg g −1 of biomass for different harvest stages), with a slight increase at the second harvest stage (bud stage, 253 µg g −1 of biomass). This observation is consistent with the reports from Mastellone et al that indicated the cannabinoid content from the stem of Cannabis sativa L. was independent of the growth stage of harvesting and the content showed a slight increase at the stage closer to flowering [11]. Free fatty acid (FFA) composition in the hemp was consistent with previous studies [42], which highlighted that palmitic acid was the most abundant FFA, followed by oleic acid and stearic acid.…”
Section: Stemssupporting
confidence: 92%
See 1 more Smart Citation
“…sativa L. were chosen due to the rich phytocomplex comprising several classes of non-volatile bioactive compounds. As reported by the authors, the main phytochemicals identified in this matrix were flavonoid glycosides and non-psychotomimetic cannabinoid acids. Previous studies on neutral HDESs composed of terpenoids compounds of natural origin have highlighted that these solvents were capable of extracting cannabinoid compounds but less effective in the enrichment of the flavonoid fraction …”
Section: Resultsmentioning
confidence: 99%
“…There are also other studies in the literature presenting the antioxidant potential of the cannabis plant. In a study by Mastellone et al, the fiber-type Cannabis sativa L. plant material was extracted with methanol and acetone by ultrasound-assisted extraction; subsequently, both of the extracts were tested for antioxidant properties with the use of the ABTS and DPPH assays [80]. Methanol extract showed a stronger antioxidant potential than acetone.…”
Section: Antioxidant Activitymentioning
confidence: 99%